THE USE OF SCAFFOLDING STRATEGY IN IMPROVING STUDENTS’ SPEAKING SKILL - Miraz Pringgadana Setiawan; Wahid Hasim (English Education and Applied Linguistics Journal (EEAL Journal), 2018)
The study investigated to discover whether scaffolding strategy can be used as an effective strategy in improving students’ speaking skill or not. This study was taken because there are many difficulties that most of students face when they learn speaking skill. So scaffolding strategy was taken because scaffolding itself is an extremely social form of instruction, with more capable peers and teacher helps student to solve some tasks (Hogan and Pressley, 1997) and it is match with what Tam (1997) said that providing students with some kind of situations and speaking task takes a significant role in improving students’ speaking skill. This study had been done on March 31st 2016 until April 28th 2016. This study is a quantitative research with pre-experimental one group pre-test – post-test design. The population of this study was the second grade of SMAN 1 Garut. The samples of this study were the students of class XI MIPA 8 with 36 students. Instrument that was used in this study is speaking test that was divided into two parts, they were pre-test that was used to test the students’ ability before the students were given the treatment and also post-test that was used to test the students’ ability after the students were given the treatment. Based on the study, it was found that the result of tobserved was 6.8359 and the result of tcritical was 2.0317. The result of the data analysis showed that tobserved = 6.8359 was placed in the area where Ha is accepted. Thus, it means that Ha is accepted otherwise Ho is rejected. There was a significant influence scaffolding strategy in improving students’ speaking skill. Based on the findings above, scaffolding can be used as an alternative teaching strategy that is effective in improving students’ speaking ability.